The Epstein-Barr Virus Latent Membrane Protein 1 and Transforming Growth Factor–β1 Synergistically Induce Epithelial–Mesenchymal Transition in Lung Epithelial Cells - Sides, Mark D. (American Thoracic Society, 2011)
The histopathology of idiopathic pulmonary fibrosis (IPF) includes the presence of myofibroblasts within so-called fibroblastic foci, and studies suggest that lung myofibroblasts may be derived from epithelial cells through epithelial–mesenchymal transition (EMT). Transforming growth factor (TGF)–β1 is expressed and/or activated in fibrogenesis, and induces EMT in lung epithelial cells in a dose-dependent manner. A higher occurrence of Epstein-Barr virus (EBV) has been reported in the lung tissue of patients with IPF. EBV expresses latent membrane protein (LMP) 1 during the latent phase of infection, and may play a role in the pathogenesis of pulmonary fibrosis inasmuch as LMP-1 may act as a constitutively active TNF-α receptor. Our data show a remarkable increase in mesenchymal cell markers, along with a concurrent reduction in the expression of epithelial cell markers in lung epithelial cells cotreated with LMP-1, and very low doses of TGF-β1. This effect was mirrored in lung epithelial cells infected with EBV expressing LMP1 and cotreated with TGF-β1. LMP1 pro-EMT signaling was identified, and occurs primarily through the nuclear factor–κB pathway and secondarily through the extracellular signal–regulated kinase (ERK) pathway. Activation of the ERK pathway was shown to be critical for aspects of TGF-β1–induced EMT. LMP1 accentuates the TGF-β1 activation of ERK. Together, these data demonstrate that the presence of EBV-LMP1 in lung epithelial cells synergizes with TGF-β1 to induce EMT. Our in vitro data may help to explain the observation that patients with IPF demonstrating positive staining for LMP1 in lung epithelial cells have a more rapid demise than patients in whom LMP1 is not detected.